Projection of diametric distribution and carbon stock of a managed forest in Manaus/AM - Souza, Cíntia Rodrigues de; Azevedo, Celso Paulo de; Rossi, Luiz Marcelo Brum; Santos, Joaquim dos; Higuchi, Niro (Floresta, 2014)
The projection of forest growth is important for forest management, to plan the subsequent cutting cycles and to show the tendencies that the forest will present in the future. This study evaluated the use of a stochastic model - the Markov Chain - in the projection of the future diametric distribution and carbon stock of a forest subjected to experimental selective logging in Manaus / AM. The data used were obtained from an experiment conducted since the 1980s by the Instituto Nacional de Pesquisas da Amazônia (Inpa). The forest inventories were conducted in the years 2005, 2007, 2009 and 2010. The main variable used was the diameter at breast height (DBH). The Markov Chain was used to project the diameter distribution and the carbon stock for 2015. With respect to the stock of carbon expected, this should exceed the existing stock in 2010, reaching about 157 t/ha. With these results it is possible to conclude that, if the dynamics projection will be confirmed, the studied forest will continue growing and increasing its carbon stock, thus acting as a CO2 sink.
Keywords: Nia